Unlocking AlN Piezoelectric Performance with Earth‐Abundant Dopants. (2nd February 2023) - Startt, Jacob; Quazi, Mohammed; Sharma, Pallavi; Vazquez, Irma; Poudyal, Aseem; Jackson, Nathan; Dingreville, Remi
Abstract: The increasing demand for high‐performance piezoelectric materials and toxicity and thermal stability issues of the widely used lead zirconate titanates (PZT) have spurred a search for better alternatives in electronic devices. In comparison to PZT, group III nitrides such as aluminum nitride (AlN), are only weakly piezoelectric, but doping AlN with scandium (Sc) improves the piezoelectric response by nearly 500%. Relative to PZT, doped‐AlN piezoelectric materials are advantageous because they are far more compatible with complementary metal–oxide–semiconductor (CMOS) materials, and they maintain both piezoelectric and thermodynamic stability up to very high temperatures. Unfortunately, rare‐earth metals are notoriously expensive, and fabricating stable films with rare‐earth dopants is also challenging, limiting their use in industrial applications. In this work, ab initio calculations are combined with targeted fabrication and experimentation to identify alternative earth‐abundant dopants for AlN from the periodic table d‐block. Amongst the 23 elements screened, it is found that group IVB metals, titanium, zirconium, and hafnium induce large piezoelectric enhancements comparable to Sc. This improvement is traced to shifts in the atomic sublattice structure and changes in the local charge states. In demonstrating a highly accessible and affordable path for technological adaptation of AlN‐based piezoelectrics, this work provides the foundation for sustainable, next‐generation electronics. Abstract : Harnessing strong piezoelectric performance in complementary metal–oxide–semiconductor compatible, aluminum nitride (AlN) thin film materials will open the door to many currently inaccessible piezoelectric capabilities. In this work, it is demonstrated, both theoretically and experimentally, that doping AlN with common and affordable group IVB transition metals (Ti, Zr, and Hf) yields impressive piezoelectric enhancements on par with that of much more expensive and rare Sc and Yb rare‐earth metals.